Heat transfer in Ar and N2 doped solid CO - Romanova, T.V.; Stachowiak, P.; Jeżowski, A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2015)
The measurements of thermal conductivity coefficient of a solid carbon monoxide crystal containing argon and nitrogen admixtures at different concentrations (1.5, 3, 6, 12.5, 25% for N2 and 0.5, 1, 1.25, 2, 4% for Ar) were performed in the temperature range from 1.5 to 40 K by steady-state heat flow method. For analysis of the experimental data the Callaway method in the framework of the Debye model was used. The contribution of various mechanisms of phonon scattering, including scattering by disordered dipoles of the CO matrix, to the thermal conductivity of CO–N2 and CO–Ar solid solutions were taken into account.